Abdominal Drainage in Complicated Appendicectomy - Resources Down the Drain? - Nazarian, Scarlet; Boardman, Charlotte; Chohda, Ezzat; Shah, Ankur (Journal of Nepal Health Research Council, 2021)
Background: There is currently no clear consensus on the use of drains during an appendicectomy to prevent abscess formation. Our aim was to ascertain whether the use of drains in complicated appendicitis reduces post-operative complications and length of stay.Methods: We performed a retrospective review of patients with complicated appendicitis undergoing appendicectomy from March-November 2018. Complicated appendicectomy (perforated or gangrenous appendicitis) patients were divided into two groups; with drain Group 1 (G1) and no drain Group 2 (G2). Groups were compared for post-operative complications and length of stay. Results: Out of a total 76 patients, 26 (34%) had drain (G1) and 50 (66%) had no drain (G2). The pre-operative CRP in G1 vs. G2 (124.8 vs. 48.3, p= 0.02); post-operative complication 9 (34.6%) vs. 6 (12%), p=0.019); intra-abdominal abscess 5 (19.2%) vs. 3 (6%), p=0.07 and LOS 5.5 days vs. 3 days, p=0.0001 were significantly higher in patients with a drain.Conclusions: The use of an intra-operative drain in complicated appendicitis increases the risk of a post-operative complication and increases length of stay.Keywords: Appendicectomy; complicated appendicitis; drain